The Effectiveness of The Sharia Supervisory Board’s Role: Study on The Islamic Banks in Indonesia - Wijayanti, Rita; Falikhatun, Falikhatun (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to investigate the relationship between the characteristics and effectiveness of the Sharia Supervisory Board’s (SSB) role in Islamic Banks (IBs). To justify the qualitative study, legal documents, annual reports, books, journals, and previous research were examined. Eight SSB characteristics were also reviewed to see how they affected the effectiveness of the SSB’s role in 14 IBs in Indonesia. This study uses the characteristics of SSB as a whole so that it is sufficient to explain the effectiveness of the role of SSB in Islamic Banks. As an additional analysis, the SSB characteristics on SOE-owned IBs before and after the merger were also presented. The research findings show that the dual positions of SSB members and the lack of accounting and financial competence need the government's attention in setting the rules.